Key Themes for the Global Energy Economy in 2024 - Oxford Institute for Energy Studies (OIES) (The Oxford Institute for Energy Studies, 2024)
This year's key themes outlook focuses heavily on the resilience of hydrocarbon markets in the face of disruptions of many kinds; how sustainability and energy transition are becoming a strategic political objective that reaches well beyond the energy economy; and the technology elements of that transition where we see significant movement in the next 12 months. In an ever more uncertain world, energy policy increasingly finds itself on the front line of election politics - significant in one of the densest election cycles for years. There is an abundance of moving parts in global energy economy and this report discusses those key elements - as seen through the lens of the energy trilemma, or even dilemma which we argue is evolving in 2024.
Keywords: 330; Carbon; CCS; CDR; China; COP28; elections; Energy Transition; European gas demand; European gas supply; Flexibility; Geopolitics; Hydrogen; LNG; Offshore wind; Oil Demand; OPEC